2014
DOI: 10.1080/10437797.2014.947162
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Values in Human Services Administration: Implications for Social Work Education

Abstract: The perceived wisdom in the social work education community, based on empirical research from the 1990s and the early part of this century, says that the master of social work (MSW) degree is not competitive with the master of business administration or the master of public administration to obtain top-level administration jobs in nonprofit agencies. This article reviews recent information on hiring preferences of board chairs that provides new hope that the MSW degree with a concentration in management or adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This outcome is consistent with previous literature. Indeed, Watson and Hoefer (2014) also reported the impact of forming a conducive environment for engagement in a campus retrieval house for young adults. The study explored that a welcoming atmosphere instead of hostile spaces led to quicker recovery or the attainment of results.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is consistent with previous literature. Indeed, Watson and Hoefer (2014) also reported the impact of forming a conducive environment for engagement in a campus retrieval house for young adults. The study explored that a welcoming atmosphere instead of hostile spaces led to quicker recovery or the attainment of results.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout history, social workers have applied these values to successful practice in many domains. Recent studies illustrate how incorporation of social work values helped juvenile offenders improve their case outcomes (Prinsloo, 2014), improved services in community mental health centers (Brophy & McDermott, 2013), encouraged human service administrators to become stronger leaders (Watson & Hoefer, 2014), refined family centered health care (Craig, Betancourt, & Muskat, 2015), promoted self-determination for members of the LGBT+ population (Erdley, Anklam, & Reardon, 2014), and provided insight on working with members of the military community (Olson, 2014). This list of recent articles illustrates the diversity of clients social workers serve through their value-based practice.…”
Section: Social Work Valuesmentioning
confidence: 99%
“…included "communication, developing and managing many different kinds of relationships, financial management, dedication to the mission, vision and future orientation, leadership, management skills, and integrity and ethics" (Hoefer et al, 2013, p. 441). Additionally, in a second study of board chairs, Watson and Hoefer (2014) found that these executives viewed client awareness and understanding as a critical component to leading the organization, echoing Suarez's (2010) assertion that nonprofit knowledge is needed to be an effective nonprofit CEO.…”
Section: The Experience Of Leading Nonprofit Organizationsmentioning
confidence: 97%
“…Many of these programs have heeded researcher's calls to increase focus on the skills necessary to successfully lead complex nonprofit organizations (Saidel & Smith, 2015;Young & Grinsfelder, 2011). Thus, as researchers of nonprofit organizations have attempted to define what skills one needs to lead, higher education has simultaneously endeavored to meet this leadership learning crisis by enhancing the education opportunities for the next generation of leaders (Goldkind & Pardasani, 2013;Mirabella, 2007;Watson & Hoefer, 2014).…”
Section: Higher Educationmentioning
confidence: 99%